No fortunate son [large type] : a Pike Logan thriller - Taylor, Brad, 1965- (Taylor, Brad, 1965- Pike Logan thriller., 2015)
Veteran operator Pike Logan and partner Jennifer Cahill are expecting orders for their next mission. Instead, they learn that their latest actions have gotten them fired, despite having saved thousands of innocent lives. But Pike's shock and fury is redirected when their commander, Colonel Kurt Hale, asks him and Jennifer for help with a personal matter: His niece Kylie, an exchange student in England, has gone missing.